Measurements of Z→vv+jets to Z→ll+jets differential cross section ratios in pp collisions at √s = 13 TeV using the ATLAS Detector - Son, Hyungsuk. (Tufts University. Tisch Library., 2019)
This thesis presents measurements of the Z→vv+jets to Z→ll+jets differential cross section ratios as a function of various observables using proton-proton collisions at a center of mass energy of √s = 13 TeV. Since the Z→vv+jets process is very similar to the Z→ll+jets process for QCD effects and jet kinematics, many experimental and theoretical uncertainties on the modeling of the SM events will cancel in the ratio. Each of the measured ratios is unfolded to be comparable to the corresponding theoretical predictions without the detector effects. With these techniques, two analyses were carried out based on the data collected by the ATLAS experiment and used to get the results presented in this thesis. The first analysis consists of two measurements of the ratio of Zpt distribution, a QED measurement and a measurement of the invisible width of the Z. This analysis used the full 2015+2016 dataset with a total integrated luminosity of 36.2 fb-1. Preliminary results for the QED measurement show that the QED FSR modeling provides a fair description of electron data and excellent agreement with data in the muon channel. The invisible width of the Z is also extracted using the measured unfolded ratio. A precision comparable to LEP most precise results have been obtained, improving the overall precision on the direct determination of this parameter by about 40%. The purpose of the second analysis is to search for beyond the Standard Model (BSM) physics. This analysis describes a measurement of detector-corrected observables sensitive to the anomalous production of events with jet and large missing transverse momentum in pp collisions using 3.2 fb-1 of data collected in 2015. The measured ratios are found to be in agreement with the Standard Model prediction and the data is used to place limits on various theoretical models for dark matter production. The limits in simplified models are competitive with detector-level approaches and provide improved sensitivity to models in which the dark matter mass is close to half the mediator mass.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Physics.; Advisor: Pierre-Hugues Beauchemin.; Committee: Gary Goldstein, Krzysztof Sliwa, Cristian Staii, and Benjamin Brau.; Keywords: Particle physics, and Physics.